RARE SURVIVAL BY SHOT GUN INJURY (Journal of Forensic Medicine & Toxicology, 2011)
In this report authors present a unique case of accidental firearm injury by a country made Firearm weapon. A case of accidental shotgun injury by a 50-year old man while traveling in a tractor. The victim had multiple (>70) pellets injury over the face, four pellets on the neck and two pellets on right hand. Surgical intervention was performed to remove the pellets. A markedly multiple (38) pellets were recovered from the face and hand. Even after this, victim had been left out with some pellets in face which were not possible for a surgeon to remove. Victim survived with some of the pellets intact even in the vital area, which is a rare one.
Keywords: Country made shot gun; Fire arm wounds; Accidental injury